2017
DOI: 10.15376/biores.12.4.8870-8885
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-bed system for adsorption of anionic acid dyes from binary solution onto quaternized kenaf core fiber

Abstract: Water pollution due to the effluents from textile industries causes serious concern around the world. During the coloration process, the excess synthetic dyes are discharged into the wastewater stream. In the present research, kenaf core fiber (KCF) residue was chemically modified with (3-chloro-2-hydroxypropyl) trimethylammonium chloride (CHPTAC) to alter the surface properties and increase the surface area to develop more active sites that capture anionic dyes from aqueous solution. Fixed-bed adsorption stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For greater operating times (up to achieving the saturation point), the column might be included in a system of adsorption columns connected consecutively. It should be noted herein that for industrial applications the adsorbent column is usually replaced when the relative concentration C t /C 0 is equal to value 0.5, that is, 50% breakthrough is attained [39]. For our application (wool fibers/BB9), the relative concentration of 0.5 (i.e., 50% breakthrough) was achieved after 780 min contact time, operating at the inlet flow rate of 3.0 mL/min.…”
Section: Model Model Equation Model Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…For greater operating times (up to achieving the saturation point), the column might be included in a system of adsorption columns connected consecutively. It should be noted herein that for industrial applications the adsorbent column is usually replaced when the relative concentration C t /C 0 is equal to value 0.5, that is, 50% breakthrough is attained [39]. For our application (wool fibers/BB9), the relative concentration of 0.5 (i.e., 50% breakthrough) was achieved after 780 min contact time, operating at the inlet flow rate of 3.0 mL/min.…”
Section: Model Model Equation Model Parametersmentioning
confidence: 95%
“…In our study involving coarse wool fibers loaded with BB9 dye, the results of adsorption performance under batch conditions fall somewhere in the middle when compared to findings from other studies listed in Table 4. Regarding fixed-bed adsorption, fibrous materials, other than wool, had been reported for the retention of dyes, such as amino-modified cotton fibers [37], bagasse treated with tartaric acid [38], and chemically modified kenaf core fibers [39] (see Table 4). For fibrous materials like modified cotton [37], it was observed that the adsorption capacity was less for fixed-bed adsorption when compared to batch adsorption for the same system.…”
Section: Model Model Equation Model Parametersmentioning
confidence: 99%
“…Its chemical structure is described in Fig. 2, and the physicochemical properties are given in Table 1 (Idan et al, 2017).…”
Section: Adsorbatementioning
confidence: 99%
“…Many of these dyes, especially organic ones, can be toxic, carcinogenic, mutagenic, and may affect aquatic life (Idan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%